ANALISIS YURIDIS PEMBERHENTIAN TIDAK HORMAT ANGGOTA KEPOLISIAN YANG MELAKUKAN TINDAK PIDANA UNTUK MEWUJUDKAN PERLINDUNGAN DAN KEPASTIAN HUKUM (STUDI PENELITIAN DI KEPOLISIAN RESOR BARELANG KOTA BATAM) - Norista Norista; Ramlan Ramlan; Siti Nurkhotijah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The enforcement of police discipline and code of ethics is very much needed in order to realize the implementation of the tasks assigned and achieve the professionalism of the Police. It is very unlikely that law enforcement can run well, if the law enforcers themselves are undisciplined and unprofessional. The problems in this research are; What is the Legal Arrangement for Disrespectful Dismissal of Police Members Who Commit Crimes in Indonesia?; What are the legal arrangements regarding the disrespectful dismissal of members of the police who commit criminal acts to realize legal protection and certainty?; How is the implementation and the factors that become obstacles as well as solutions to the disrespectful dismissal of police officers who commit criminal acts to realize legal protection and certainty (Research Study at the Barelang Resort Police). The results showed that; Legal arrangements for Disrespectful Dismissal of Police Members Who Commit Criminal Acts in Indonesia have been implemented well, but revisions are still needed in terms of emphasizing violations of the code of ethics, both criminal and civil; Implementation and factors that become obstacles and solutions for dishonorable dismissal of police officers who commit criminal acts to realize legal protection and certainty (Research Studies at the Barelang Police Resort), have been carried out well, in fact there have even been several police officers who have received sanctions in accordance with the required actions. he did; The obstacle experienced by Poresta Barelang in Batam City in upholding the police code of ethics is the changing laws and regulations and giving rise to multiple interpretations. The level of discipline of Polri members is still lacking, leaders who do not pay attention to violations and support from the Information Sector are slow. The conclusion in this study is the application of dishonorable discharge of police officers who commit criminal acts or violations of the POLRI's professional code of ethics against which they are subject to internal sanctions in the form of disciplinary sanctions consisting of dishonorable discharge.. Based on the data analysis carried out, it was concluded that guaranteeing the education rights of children who are serving a sentence at the Special Guidance Institution (LPKA), the solution taken by the government is to increase the budget for education organized by the Child Special Guidance Institution (LPKA), increase human resources Humans (HR) who organize education at LPKA are teachers who are competent in their fields and provide space for children who are undergoing punishment to be creative in education according to their talentsKeywords: PTDH, Police, Crime, Protection, Legal Certainty.